Interparental Conflict and Adolescents’ Relational Aggression and Loneliness: The Mediating Role of Maternal Psychological Control - Koçak, Aylin; Mouratidis, Athanasios; Sayıl, Melike; Kındap-Tepe, Yeliz; Uçanok, Zehra (Journal of Child and Family StudiesJournal of Child and Family Studies, 2017)
Research has shown that frequent, intense, and poorly resolved conflict between parents relates to adolescents’ adjustment problems but the mechanisms that explain such a link have not been fully uncovered. In this prospective study, we relied on the spillover hypothesis and investigated through an integrated multi-informant model whether maternal psychological control would account for the associations between interparental conflict and adolescents’ relational aggression and loneliness. Participants were 527 Turkish adolescents (M age = 14.36 years, SD = 0.33) and 307 mothers (M age = 41.18 years, SD = 4.47). Analyses through structural equation modeling indicated that interparental conflict (as assessed by both the adolescents and their mothers) related positively to maternal psychological control (as assessed again by both of them) which in turn predicted adolescent-reported relational aggression and loneliness, 8 months later. These findings are in line with the spillover hypothesis and show that dysfunctional relationships between parents are related to poor parenting practices and in turn to adolescents’ maladjustment.